A comparative binding mechanism between human serum albumin and α-1-acid glycoprotein with corilagin: biophysical and computational approach. Issue 46 (22nd April 2016) - Yeggoni, Daniel Pushparaju; Rachamallu, Aparna; Subramanyam, Rajagopal
Abstract : The interaction between corilagin and serum proteins was studied by biophysical and molecular dynamics techniques which in turn provides valuable information about the interaction of phytochemical corilagin with serum proteins. Abstract : The binding of corilagin with plasma serum proteins like human serum albumin (HSA) and α-1-acid glycoprotein (AGP) was investigated under physiological conditions. To understand the pharmacological importance of the corilagin molecule, anti-inflammatory activity on mouse macrophages (RAW 264.7) cell lines was studied. This study reveals that corilagin caused an increase in inhibition growth of inflamed macrophages in concentration-dependent manner with an IC50 value of 66 μM. Further, intrinsic fluorescence of HSA and AGP was quenched upon titration of corilagin, and the binding constants obtained from fluorescence emission was found to be K corilagin 4.2 ± 0.02 × 10 5 M −1 which corresponds to the free energy of −7.6 kcal M −1 at 25 °C for a HSA–corilagin complex. Interestingly, corilagin showed binding with AGP, an acute phase protein, and the binding constant was found to be K corilagin = 1.5 ± 0.01 × 10 4 M −1 and its free energy was −5.6 kcal M −1 at 25 °C. Further, the average binding distance, r, between the donor (HSA) and acceptor (corilagin) was calculated and found to be 1.32 nm according to Förster's theory of non-radiation energy transfer. Later, circular dichroism studies emphasized that there are marginal changes in secondary structural conformation of HSA in the presence of corilagin. Corilagin is specifically bound to site I of HSA which was proved by site specific marker, phenylbutazone. Furthermore, the binding details between corilagin and HSA revealed that corilagin was bound to subdomain IIA through multiple interactions like hydrogen bonding and hydrophobic effects. Molecular dynamic studies (MD) also suggest that binding is very precise to site I (IIA domain) on HSA. Also, MD studies showed that HSA–corilagin complex reaches equilibration state at around 4 ns, which proves that the HSA–corilagin complex is stable in nature, hence the experimental and computational results are in agreement. Thus, examining the interaction mechanism of corilagin with plasma proteins may play a critical role in developing corilagin inspired drugs.